Efek ekstrak minyak citronela Cymbopogon nardus L. terhadap proporsi frekuensi kontak fisik Musca domestica L. (Diptera: Muscidae) pada ransum dan performa broiler - Laurentius Rumokoy; Charles Kaunang; Wisje Toar (Perhimpunan Entomologi Indonesia, 2017)
Flies are well known as vector that has an important role in transferring pathogen microbes to broilers. Various tropical plants, as well as Cymbopogon spp. possess a large potential in controlling the activities of this flies. This research was aimed to determine the effect of citronella oils extracted from Cymbopogon nardus L on Musca domestica L. (Diptera: Muscidae) activities in ration surface and also to study the effect of COE in ration on broiler performances. Three treatment levels of EMC were 0%, 0.25%, and 0.5% and added in broilers ration experimental. The research was designed by using randomized experimental design. The parameters measured were: proportion of physical contact frequency (PCF), feed consumption, and body weight gain. The results showed that the treatment levels of COE of C. nardus significantly influenced (F2,48 = 38,456, P=0,000) PCF of M. domestica, while the levels of COE were significantly influencing (F2,36 = 51,178, P = 0,000) the feed consumption and body weight gain of broilers (F2,36 = 81,969, P=0,000). This research revealed that the levels of COE of C. nardus were able to decrease PCF value of M. domestica in ration while the treatments increased feed consumption and body gain values of broilers. We concluded that EMC of C. nardus L up to 0.5% can function as bio-repellent to the M. domestica activities on broiler ration and cause a positive effect to the consumption and to the body gains of chickens broilers.